2017
DOI: 10.1088/1681-7575/aa6ab3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic evaluation of contemporary impurity correction methods in ITS-90 aluminium fixed point cells

Abstract: The fixed points of the International Temperature Scale of 1990 (ITS-90) are the basis of the calibration of standard platinum resistance thermometers (SPRTs). Impurities in the fixed point material at the level of parts per million can give rise to an elevation or depression of the fixed point temperature of order of millikelvins, which often represents the most significant contribution to the uncertainty of SPRT calibrations. A number of methods for correcting for the effect of impurities have been advocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…As shown in table 1, for each sample, the impurity compositions obtained from different analysis laboratories showed poor consistency in terms of the detected elements and the concentrations, which may lead to significant discrepancies in the SIE corrected fixed-point temper atures. As similar inconsistencies have also been reported in several publications for different fixed-point substances [1,32,36], it is of paramount importance to assess the correctness and consistency of the chemical assay by comparing the measured difference in the fixed-point temperatures with the calculated difference in the SIE corrections before correcting for the impurity effect. Resistance ratios of the liquidus temperatures and the freezing temperatures, for which the SIE correction were applied, or the impurity effect was not corrected but its overall effect was given as the uncertainty factor (i.e.…”
Section: Difference Between the Fixed-point Temperatures Of The Diffe...supporting
confidence: 65%
See 1 more Smart Citation
“…As shown in table 1, for each sample, the impurity compositions obtained from different analysis laboratories showed poor consistency in terms of the detected elements and the concentrations, which may lead to significant discrepancies in the SIE corrected fixed-point temper atures. As similar inconsistencies have also been reported in several publications for different fixed-point substances [1,32,36], it is of paramount importance to assess the correctness and consistency of the chemical assay by comparing the measured difference in the fixed-point temperatures with the calculated difference in the SIE corrections before correcting for the impurity effect. Resistance ratios of the liquidus temperatures and the freezing temperatures, for which the SIE correction were applied, or the impurity effect was not corrected but its overall effect was given as the uncertainty factor (i.e.…”
Section: Difference Between the Fixed-point Temperatures Of The Diffe...supporting
confidence: 65%
“…the liquidus slope or the distribution coefficient). The difficulty of obtaining the former, by chemical assay, has been well documented and is still considered challenging due to the inconsistency in the results of the chemical assays [6,32,34,36]. On the other hand, the liquidus slopes and distribution coefficients have recently been well characterized and the situation continues to improve [1][2][3]35].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, even when a number of independent laboratories agreed that a contaminant was present, the manufacturers assay may (though not always) give a much lower reading. In only one case in [8], though, was an impurity detected by two independent laboratories at levels substantially above the detection limits that was not also showing a high value in the third. It seems that false positives are common, but not false negatives.…”
Section: Impuritiesmentioning
confidence: 85%
“…Reliable measurement of low levels of contaminants is far from being routine. Taking the data from a recent study [8], a number of confounding problems are found. Firstly, particular laboratories consistently found particular elements across multiple samples which were not found by other laboratories.…”
Section: Impuritiesmentioning
confidence: 99%
“…Impurities in pure metal substances are a major source of uncertainty in realising the International Temperature Scale of 1990 (ITS-90) [3] fixed-point temperatures [2]. There are several techniques for accounting for the influence of impurities [4,5] and these have recently been compared using an aluminium fixed point [6]. A key technique for quantifying the effect of given impurities is the Sum of Individual Estimates (SIE) method [4,5,7,8].…”
Section: Introductionmentioning
confidence: 99%